2009
DOI: 10.1158/1055-9965.epi-09-1014
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Human Smoking Behavior and Machine Smoking Patterns: Implications for Understanding Smoking Behavior and the Impact on Laboratory Studies

Abstract: Background: Recent Food and Drug Administration legislation enables the mandating of product performance standards for cigarette smoke and the evaluation of manufacturers' health claims for modified tobacco products. Laboratory studies used for these evaluations and also for understanding tobacco smoke toxicology use machines to generate smoke. The goal of this review is to critically evaluate methods to assess human smoking behavior and replicate this in the laboratory. Methods: Smoking behavior and smoking m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 135 publications
1
100
0
Order By: Relevance
“…However, because no single smoking machine regimen will adequately reflect human smoking behavior (Institute of Medicine 2001; Baker, 2002;Borgerding and Klus, 2005; World Health Organization Study Group on Tobacco Product Regulation, 2007Regulation, , 2008, only poor correlations exist between smoke nicotine yields determined using machinesmoking protocols and nicotine-derived biomarker of exposure estimates in smokers (Russell et al, 1980;Rickert and Robinson, 1981;Benowitz and Jacob, 1984;Gori and Lynch, 1985;Diding, 1987;Andersson et al, 1997;Byrd et al, 1998;Jarvis et al, 2001;Ueda et al, 2002;Scherer et al, 2007;Mendes et al, 2009;Lindner et al, 2011). Consequently, the U.S. Federal Trade Commission (FTC) has officially rescinded its guidance for reported smoking machine tar and nicotine yields (Federal Trade Commission, 2008b), while increased interest has occurred within the tobacco control community to develop alternative protocols which better reflect smoker exposure to harmful and potentially harmful constituents (HPHC) (World Health Organization Study Group on Tobacco Product Regulation, 2004Hammond et al, 2006Hammond et al, , 2007Marian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, because no single smoking machine regimen will adequately reflect human smoking behavior (Institute of Medicine 2001; Baker, 2002;Borgerding and Klus, 2005; World Health Organization Study Group on Tobacco Product Regulation, 2007Regulation, , 2008, only poor correlations exist between smoke nicotine yields determined using machinesmoking protocols and nicotine-derived biomarker of exposure estimates in smokers (Russell et al, 1980;Rickert and Robinson, 1981;Benowitz and Jacob, 1984;Gori and Lynch, 1985;Diding, 1987;Andersson et al, 1997;Byrd et al, 1998;Jarvis et al, 2001;Ueda et al, 2002;Scherer et al, 2007;Mendes et al, 2009;Lindner et al, 2011). Consequently, the U.S. Federal Trade Commission (FTC) has officially rescinded its guidance for reported smoking machine tar and nicotine yields (Federal Trade Commission, 2008b), while increased interest has occurred within the tobacco control community to develop alternative protocols which better reflect smoker exposure to harmful and potentially harmful constituents (HPHC) (World Health Organization Study Group on Tobacco Product Regulation, 2004Hammond et al, 2006Hammond et al, , 2007Marian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When generating cigarette smoke through a smoke machine, there are several international standards. These standards are important since the rate and duration that air passes through a cigarette affects the burn temperature and the relative amount of chemicals that are subsequently produced (68,99), and this is likely true for E-Cigs. Also, smoking tobacco in a reproducible fashion facilitates cross-laboratory data comparisons.…”
Section: Tissue/cell Type Effectsmentioning
confidence: 99%
“…For example, the Federal Trade Commission/International Standard Organization protocol calls for 2 s/35 ml puff every 60 s, and this is likely the most common puff profile used in the laboratory. However, it has been suggested that this profile underestimates how much people actually inhale, and a second profile, called "Canadian Intense," which uses 2 s/55 ml puff every 30 s, has also been adopted, and it has recently been recommended that experiments be repeated with both profiles to study smoke generation over the range of exposures (68,99). Similarly, for E-Cigs, knowing user's puff topography characteristics will be important for setting smoke machine parameters in the laboratory and for studying appropriate E-Cig emissions.…”
Section: Tissue/cell Type Effectsmentioning
confidence: 99%
“…Modifying the design and content of cigarettes to reduce exposure to toxicants, for example those comprising tar, can also reduce nicotine yield measured by standard FTC smoking machine methods (Armitage et al, 1975); however, to meet nicotine needsblood nicotine levels sufficient to be satisfying-smokers have been shown to ''compensate'' for the reduced nicotine yield by altering their smoking behavior to increase the effective nicotine yield of the modified product (Benowitz, 2001b;Marian et al, 2009;Scherer, 1999;West et al, 1984;Zacny and Stitzer, 1988). A consequence of these nicotine-need driven behavioral changes-deeper, larger or more frequent puffs-is the potential for greater exposure to the toxicants comprising tar, as well as nicotine, compared to the unmodified cigarette Scherer, 1999;Zacny and Stitzer, 1988).…”
Section: Discussionmentioning
confidence: 99%